Tradícionális termékek emocionális megközelítésben - Ferencz, Árpád; Nótári, Márta (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
Traditional Hungarian foods get successfully to consumers if these products are sold on a special market. In our research we set a hypothesis that the decisions, what traditional food consumers make, are based on imperfect information. Place of purchase is an influential factor. Based on this assumption we examined the followings in a questionnaire survey: Where do customers like to buy these products?, Is there an appropriate market for these products?, What are the attributes of this market? The basic aim of our research was to know how special quality single and differentiated products can stay safely on the market. Consumer segmentation seemed to be a good way to know this, but even some members of the same segment can have different purchase decisions. Personal life style determines this deviation. The subject of our research was to see how effective segmentation influences the dynamics of consumer product choice.